Corporate Social Responsibility and SME Internationalization: Insights from the Food Industry - Colovic, Ana; Henneron, Sandrine (Management international / International Management / Gestiòn Internacional, 2018)
Drawing on the internationalization literature, stakeholder theory and the literature linking Corporate Social Responsibility (CSR) and international business, we study how CSR influences SME internationalization and how internationalization influences CSR adoption by SMEs. We used qualitative methods to study these processes in four SMEs in the agro-food industry. Our findings indicate that internationalization significantly influences CSR adoption by SMEs, while CSR influences the speed and scope of internationalization.